Physicochemical, cooking quality and sensory characterization of yellow alkaline noodle: impact of mango peel powder level - Z., Nur Azura; S., Radhiah; W.I., Wan Zunairah; Z. A., Nurul Shazini; M. R., Ismail-Fitry (Rynnye Lyan Resources, 2020)
Mango peel comprises of 7-25% of mango fruit that contributes to the environmental pollution. Mango peel contains nutraceutical compounds that are useful as a functional ingredient to increase nutritional properties in Asian staple food, which in our case was yellow alkaline noodle. The objective of this research was to study the effect of mango peel powder at different levels (0%, 10%, 20%, and 30%) on the cooking, physicochemical and sensory properties of yellow alkaline noodles (YAN). Substitution of wheat flour with mango peel powder significantly increased 2 to 15 times fibre content in the YAN compared to control. Additionally, fat and carbohydrate were reduced by 8-45% and 6-25%, respectively. The lowest cooking quality was observed in YAN incorporated with 30% mango peel powder, which showed the highest cooking lost (20.45%) and the lowest cooking yield (163.7%). YAN with mango peel powder had decreased lightness (L*) and yellowness (b*). All of the texture profile was negatively affected by an increment of mango peel powder in YAN but showed no significant differences. Sensory attributes of YAN with the incorporation of mango peel powder up to 20% showed similar acceptance with the control. The YAN with 30% mango peel powder had significantly lower sensory acceptance of panelists than other YAN samples. The study suggests that mango peel powder substitution up to 20% is suitable to increase nutritional properties of YAN with minimal adverse effects on the cooking quality, textural properties and sensory attributes.